2011
DOI: 10.1158/0008-5472.can-10-1343
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Androgen Receptor by Intratumoral Bioconversion of Androstanediol to Dihydrotestosterone in Prostate Cancer

Abstract: The androgen receptor (AR) mediates the growth of benign and malignant prostate in response to dihydrotestosterone (DHT). In patients undergoing androgen deprivation therapy for prostate cancer, AR drives prostate cancer growth despite low circulating levels of testicular androgen and normal levels of adrenal androgen. In this report, we demonstrate the extent of AR transactivation in the presence of 5a-androstane-3a,17b-diol (androstanediol) in prostate-derived cell lines parallels the bioconversion of andros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(121 citation statements)
references
References 54 publications
9
111
0
1
Order By: Relevance
“…Interestingly, animal models have indicated that resistance to abiraterone treatment may be due to increase in the expression of its target, Cyp17A1, as well as higher expression of AR and AKR1C3 (8). Moreover, the back door pathways (29)(30)(31) to synthesize DHT (Fig. 1A, filled arrows) despite treatment with abiraterone (29) require 17b-HSDs for biosynthesis of potent androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, animal models have indicated that resistance to abiraterone treatment may be due to increase in the expression of its target, Cyp17A1, as well as higher expression of AR and AKR1C3 (8). Moreover, the back door pathways (29)(30)(31) to synthesize DHT (Fig. 1A, filled arrows) despite treatment with abiraterone (29) require 17b-HSDs for biosynthesis of potent androgens.…”
Section: Discussionmentioning
confidence: 99%
“…Rabbit polyclonal antibody for HSD17B4 was obtained from GeneTex (Irvine, CA, USA), and rabbit polyclonal antibody for HSD17B6 was obtained from Abcam (Cambridge, MA, USA) 41,42 . Both anti-HSD17B4 and HSD17B6 antibodies were used for immunohistochemistry at 8 mg/ml.…”
Section: Ddctmentioning
confidence: 99%
“…Because of this discrepancy biochemical function rather than structural similarity may be a worthwhile point to consider when extrapolating the significance of 17␀HSD subtypes between mouse and man. Recently, the increased 17␀HSD6 expression in prostate cancer was associated with the activation of back door pathway of steroid synthesis [217] and decreased 17␀HSD2 and increased 17␀HSD3 [218] expression was observed in prostate cancer specimens. However, these pathways are not yet characterised in murine PCa models.…”
Section: Relationship Between the Mouse And The Human Prostatementioning
confidence: 99%